2022
DOI: 10.1111/aphw.12386
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic growth in people affected by an occupational accident: A longitudinal multilevel model of change

Abstract: This study analyzed a predictive model of posttraumatic growth (PTG) in a cohort of 244 workers affected by an occupational accident. A longitudinal design with three points in time (i.e., 1, 6, and 12 months after the accident) was used. PTG, posttraumatic stress symptoms (PTSS), subjective severity of the event, deliberate rumination, and seeking social support were evaluated. In addition, time since the accident, age, and gender were included as predictors in our model. Deliberate rumination and seeking soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…This result As hypothesized, negative emotional expressivity partially mediated the relationship between intrusive rumination and deliberate rumination. Given the body of literature documenting the association between intrusive rumination and negative emotions (Benjet et al, 2016;García et al, 2016;Lianchao & Tingting, 2020), the finding that intrusive rumination significantly predicted negative emotional expressivity was not surprising. According to the shattered assumptions theory, trauma exposure can challenge individuals' stable belief systems about the self, others, and the world, and lead to negative emotions (Zhen & Zhou, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This result As hypothesized, negative emotional expressivity partially mediated the relationship between intrusive rumination and deliberate rumination. Given the body of literature documenting the association between intrusive rumination and negative emotions (Benjet et al, 2016;García et al, 2016;Lianchao & Tingting, 2020), the finding that intrusive rumination significantly predicted negative emotional expressivity was not surprising. According to the shattered assumptions theory, trauma exposure can challenge individuals' stable belief systems about the self, others, and the world, and lead to negative emotions (Zhen & Zhou, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, individual empathy is related to high levels of PTG via social support obtained from others. Previous studies have also shown that social support is a critical mediator in the link between individual empathy and personal growth [ 37 , 38 , 44 ].Each individual link in this mediation model is noteworthy. For the first part of the mediation process (i.e., empathy → social support), our findings were congruent with prior reports that empathic individuals can obtain more support from others relative to non-empathic individuals [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The revised PTG model [ 5 ] regards social support as an important predictor of positive changes following traumatic events. For example, both cross-sectional and longitudinal studies have found a positive relation between social support and PTG [ 37 , 38 ] that persists even after accounting for other influencing variables [ 39 ]. A longitudinal investigation of the effect of social support on PTG during the COVID-19 pandemic found that human social support significantly predicted PTG, whereas perceived support from pets predicted PTG after a month [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to most of the evidence ( Allbaugh et al, 2016 ; Kramer et al, 2020 ; García et al, 2022 ), deliberative (but not intrusive) rumination is expected to be higher among students who score higher on PTG. Contrary to this expectation, both types of rumination failed to discriminate between the different levels of PTG.…”
Section: Discussionmentioning
confidence: 99%
“…However, while intrusive rumination about an adverse event has been found to maintain distress, deliberate rumination, aimed at understanding and problem-solving, has been proposed as a way of understanding the role of cognitive processing in PTG ( Cann et al, 2011 ). Although there is evidence supporting that deliberate rumination contributes to post-traumatic growth ( Allbaugh et al, 2016 ; Kramer et al, 2020 ; García et al, 2022 ), it is still necessary to examine the association between rumination and PTG in college students who have been victimized by bullying, as it has been suggested that different events could be associated with different patterns of PTG ( Lowe et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%